Validation of the Portuguese version of community attitudes toward people with mental illness (CAMI) [artigo] - Lopes, Inês (2022)
Stigma remains a feature that influences the lifestyle of people with mental illness. Negative attitudes, stereotypes, and discrimination are still prevalent in these people’s life. Stigma is considered a public health problem that occurs unconsciously in society, categorizing people. Portugal is the seventh-worst country concerning stigma in Mental Health. There have been few improvements in reducing stigma over time, and there is a great need to create investigations and validate instruments that measure stigma in the population. This study aims to address the gaps in the level of studies and normative instruments that measure the stigma of the Portuguese population in the face of mental illness. It, therefore, aims to adapt and validate community attitudes toward people with mental illness (CAMI) culturally and examine its psychometric properties. Method: The 27-item version of CAMI was translated and back-translated into English, which was analyzed and evaluated by a panel of experts. A sociodemographic survey and CAMI were applied in an online format, in which participated 427 adults representing the Portuguese population in general. Finally, the reliability and validity of the instrument were analyzed. CAMI showed positive values of reliability and validity but not optimal. The confirmatory factor analysis values satisfactory values that indicate good quality of fit: x2 /df=3.296; comparative fit index = 0.601; goodness of fit index = 0.817; and root mean square error of approximation = 0.073, indicates good quality of fit. Cronbach alpha was different for each factor, but it was positive. Spearman coefficient (r=–0.343) obtained a negative but consistent value. This study contributed to the achievement and validation of new measures to assess the stigma of the general population related to people with mental illness. We must continue to analyze this theme, complete the validation of this instrument, and understand the existing levels of stigma, its predominance in society, and the possible creation and implementation of new measures that support literacy in mental illness and anti-stigma.